Between the Devil and the Deep Blue Sea: Politics as a Factor in Primary and Onward Migration for British Citizens Living Long-Term in Poland (Politeja, 2025)
The experience of British citizens living in in France, Spain and Italy has been amply covered by researchers. However, very little attention has been given to British citizens living in Central and Eastern Europe. Moreover, although the impact of Brexit on Britons living in the EU has received some attention, the role of politics in general as a factor in unforced migration is relatively understudied. This paper draws on qualitative in-depth interviews conducted in the period 2019-2022 with 60 British citizens living long-term in Poland. It investigates the structural effects of politics in Poland and the UK and how its sliding doors have fostered or hindered UK citizens’ ability to move between the two countries since the political transformation of 1989. On a micro level, it also looks at the individual agency of British citizens and their attempts to negotiate the changing political landscape. This paper finds that anomic feelings connected to the political conditions in the UK have often been a contributory factor in the decision to move abroad. Despite widespread concerns about political illiberalism in Poland, the state of British politics today and the structural impact of Brexit, which prevents many citizens returning to the UK with their partners, as well as the ‘hostile environment’ for Polish migrants, fuel continuing disillusionment with the UK and a reluctance to return.